If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + 1) + -8 = 2x + 15 Reorder the terms: 5(1 + x) + -8 = 2x + 15 (1 * 5 + x * 5) + -8 = 2x + 15 (5 + 5x) + -8 = 2x + 15 Reorder the terms: 5 + -8 + 5x = 2x + 15 Combine like terms: 5 + -8 = -3 -3 + 5x = 2x + 15 Reorder the terms: -3 + 5x = 15 + 2x Solving -3 + 5x = 15 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -3 + 5x + -2x = 15 + 2x + -2x Combine like terms: 5x + -2x = 3x -3 + 3x = 15 + 2x + -2x Combine like terms: 2x + -2x = 0 -3 + 3x = 15 + 0 -3 + 3x = 15 Add '3' to each side of the equation. -3 + 3 + 3x = 15 + 3 Combine like terms: -3 + 3 = 0 0 + 3x = 15 + 3 3x = 15 + 3 Combine like terms: 15 + 3 = 18 3x = 18 Divide each side by '3'. x = 6 Simplifying x = 6
| (2x+5)(7x-8)=0 | | 26(3c+4)=2(c+5)+c | | 14c^2-33cr+18r^2=0 | | 4+16x=72 | | 5(d+4)=10-5x+3 | | -10-(-7)+4=v | | 9+6x+9x-30= | | 3a^2-3p^2=0 | | 3X+12=4X-2 | | 4f-3+7f=31 | | X+2+4x-142=180 | | 3(2x-1)-3x=15 | | (x-4)=9x-33 | | 64x^2+34x+1=0 | | 5x-1=2+15 | | -2r+4=(-3)+9 | | x-2.5= | | f(t)=-3t^2+24t-36 | | 24+18x=90 | | 5x+2=3+32 | | -9=-3-n | | t^434343-t^434342=0 | | 5x-2=7x-4 | | 10-x=4x+3 | | -1=5x+6/6 | | 5x+135=0 | | 13+6x=3+11x | | 47+0.41666666666x=100 | | (64x^2-1)=0 | | -2x+4=-4x+12 | | 0=3x^2-6x-9 | | 4+7x=5x-18 |